Assessment of echocardiographic variables in severe anemic patients - Goyal, Sunita; Gupta, Hariom; Ravi Prakash Pandey; Tripathi VD (Asian Journal of Medical Sciences, 2023)
Background: Detection of left ventricular (LV) dysfunction in anemic patients using 2D strain echocardiography has been investigated inadequately. Aims and Objectives: This study was designed to compare the echocardiographic characteristics in patients with severe anemia to those without anemia using a 2D strain pattern. Materials and Methods: A cross-sectional study was conducted between April 2021 and March 2022. A total of 100 patients were incorporated in the case group, where patients with hemoglobin levels <7 g/dL, aged between 18 and 60 years, were included, whereas 100 patients with normal hemoglobin levels were included in the control group. Baseline clinical characteristics and echocardiographic parameters were studied. Results: The mean age of the case group was 38.32±14.9 years and of the control group was 39.94±14.3 years. In each group, majority of the patients were females (55%) and were from rural area. Mean hemoglobin level was 4.81±1.42 g/dL in case group and 12.41±0.9 g/dL in control group (P=0.0024). Mean peak E velocity (P=0.0002), mean peak A velocity (P<0.0001) and mean isovolumetric relaxation time (P=0.4612) represented statistically significant differences among case and control groups. The ejection fraction was 58% in the case and 56% in control group (P=0.621). Stroke volume was 58 mL in the case and 52 mL in the control group (P=0.653). LV dysfunction represented a significant difference between case and control group (Chi=28.125; P=0.0001). Furthermore, a statistically significant difference was observed between the global longitudinal strain score of the case and the control group (P=0.0015). Conclusion: Using 2D strain imaging technique, LV dysfunction was detected in severely anemic patients who had no previously detected severe cardiovascular diseases.